When Entrepreneurial Interest is Not Enough: Digital Technology Utilization as a Mediator between Entrepreneurship Learning, Entrepreneurial Interest, and Student Business Innovation - Nur Rizkiyah Dwi Ramadhani; Tuti Supatminingsih; Nurjannah Nurjannah (Journal of Economic Education and Entrepreneurship Studies, 2026)
Global digital economic transformation requires young entrepreneurs to develop innovative capabilities supported by digital technology utilization. This study aims to analyze the effect of entrepreneurship learning and entrepreneurial interest on student business innovation through digital technology utilization as a mediating variable. This study employed a quantitative approach with an explanatory survey design. The sample consisted of 361 student entrepreneurs from the Faculty of Economics and Business, Universitas Negeri Makassar, selected using purposive sampling. Data were collected using a four-point Likert-scale questionnaire and analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0. The findings show that entrepreneurship learning and entrepreneurial interest significantly influence business innovation. Digital technology utilization also mediates these relationships. These findings indicate that student business innovation is not sufficiently driven by knowledge and interest alone, but also requires digital capability as a bridge toward innovative business action.